Normative values and factors affecting Pediatric Reach Tests in Saudi children aged 6–11 years in the eastern province: cross-sectional study - Alotaibi, Reem S.; Algabbani, Maha F.; Shaheen, Afaf A. M.; Albishi, Alaa M.; Almurdi, Muneera M. (Frontiers in Pediatrics, 2024)
The Pediatric Reach Tests (PRTs) assess balance while standing-the Functional Reach Test (FRT) and Lateral Reach Test (LRT)-and in a sitting position-the Modified Functional Reach Test (MFRT) and Modified Lateral Reach Test (MLRT). Normative values have not been fully evaluated in Saudi children. The objectives are; to estimate the normative values for PRTs; investigate the correlation between the PRTs and demographic/anthropometric characteristics; and develop predictive equations for the PRTs. Methods: In this cross-sectional study, 251 children aged 6-11 were recruited. The PRTs were measured and correlated with demographic/anthropometric variables. A stepwise regression was conducted to develop the predictive equations for the PRT scores. Results: The mean and standard deviations (in cm) of the PRT scores were as follows: FRT = 20.02 ± 4.31; LRT = 13.42 ± 3.38; MFRT = 21.49 ± 4.70, and MLRT = 14.64 ± 3.66. Several significant correlations were found. Moderate correlations existed between the PRT scores and age, height, upper extremity length, lower extremity length, and foot length; there was a weak correlation with body mass index. Weight was moderately correlated with FRT and MFRT and weakly correlated with LRT and MLRT. The correlation between the base of support and LRT was moderate and was weak with FRT, MFRT, and MLRT. A weak correlation was found between sex and LRT. Age and height were the most predictive of PRT scores. Conclusion: This study provided PRT normative values that can be used as a clinical reference for evaluating balance in typically developing children.